Synthesis and Cytotoxicity of 4-Allyl-2 Methoxyphenol Derivatives - Lingga Kamadatu; Mardi Santoso (IPTEK Journal of Proceedings Series, 2015)
Synthesis and Cytotoxicity of 4-Allyl-2 Methoxyphenol Derivatives4-Allyl-2-methoxyphenol derivatives was synthesized through the application of methods of Yamaguchi in one pot with a resulting yield of 80-90%. 4-Allyl-2-methoxyphenol derivatives showed good activity in inhibiting the growth of human breast cancer cell MCF-7.